Enhanced corrosion protection and biocompatibility of a PLGA–silane coating on AZ31 Mg alloy for orthopaedic applications. Issue 115 (6th December 2016) - Agarwal, Sankalp; Morshed, Muhammad; Labour, Marie-Noelle; Hoey, David; Duffy, Brendan; Curtin, James; Jaiswal, Swarna
Abstract : This paper reports a multi-step procedure to fabricate a novel corrosion resistant and biocompatible PLGA–silane coating on the magnesium (Mg) alloy AZ31. Abstract : This paper reports a multi-step procedure to fabricate a novel corrosion resistant and biocompatible PLGA–silane coating on the magnesium (Mg) alloy AZ31. The first step involves alkaline passivation followed by dip coating in a methyltriethoxysilane (MTES) and tetraethoxysilane (TEOS) mixture to produce a cross-linked siloxane coating. The second step is to impart an amine functionalization to the silane modified surface by using 3-aminopropyl-triethoxy silane (APTES) for promoting adhesion of the acid terminated poly-(lactic- co -glycolic) acid (PLGA) as a final coating step. Static contact angle measurements, Fourier transform infrared spectroscopy and scanning electron microscopy analysis confirmed the successful assembly of coatings on the AZ31 Mg alloy. Potentiodynamic polarization and impedance spectroscopy studies showed the improved initial corrosion resistance of the coated AZ31 substrate. Measurements of magnesium ion release, pH changes and hydrogen evolution showed enhanced corrosion protection of coated substrate over uncoated AZ31 alloy for 21 and 14 days respectively. The MTT assay, live–dead cells staining, DNA quantification and alkaline phosphatase activity assay were used to measure the biocompatibility, proliferation and differentiation of MC3T3-E1 osteoblast cells. Scanning electron microscopy was used to observe cell morphology and integration with the coated surface. The coated substrate showed improved cytocompatibility as compared to the uncoated AZ31 alloy surface. The application of such coatings on biodegradable Mg alloys enhanced their corrosion resistance and biocompatibility. An additional advantage is that the coating also served as a potential delivery vehicle for specific drugs and bio-active molecules releasing from an implant surface as the coatings, such as PLGA, adapt during the corrosion process, thereby enhancing bone regeneration.